Breakwaters, coastal structures and coastlines proceedings of the international conference organized by the Institution of Civil Engineers and held in London, UK on 26-28 September 2001 - Allsop, N. W. H. 1951- (Thomas Telford, 2002)
These conference proceedings include forty-one papers from the Seventh International Conference on Coastlines, Structures and Breakwaters organised by the Institution of Civil Engineers.